2002
DOI: 10.1074/jbc.m202310200
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Tim9 and Tim10 into a Functional Chaperone

Abstract: The TIM10 complex is localized in the mitochondrial intermembrane space and mediates insertion of hydrophobic proteins at the inner membrane. We have characterized TIM10 assembly and analyzed the structural properties of its subunits, Tim9 and Tim10. Both proteins are ␣-helical with a protease-resistant central domain, and each self-associates to form mainly dimers and trimers in solution. Tim9 and Tim10 bound to one another with submicromolar affinity in equimolar amounts and assembled in a stable, significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
63
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 54 publications
3
63
0
1
Order By: Relevance
“…The TIM10 complex, composed of Tim9 and Tim10 proteins subsequently binds to AAC, mediating the passage of the hydrophobic carrier across the intermembrane space (13)(14)(15)(16)(17)(18). In doing so, the TIM10 complex presumably prevents aggregation in the aqueous intermembrane space in agreement with a recently demonstrated chaperonelike function in vitro (19). This carrier-chaperone complex is then guided to Tim12, which is peripherally attached to the outer surface of the inner membrane (stage IIIb).…”
mentioning
confidence: 49%
“…The TIM10 complex, composed of Tim9 and Tim10 proteins subsequently binds to AAC, mediating the passage of the hydrophobic carrier across the intermembrane space (13)(14)(15)(16)(17)(18). In doing so, the TIM10 complex presumably prevents aggregation in the aqueous intermembrane space in agreement with a recently demonstrated chaperonelike function in vitro (19). This carrier-chaperone complex is then guided to Tim12, which is peripherally attached to the outer surface of the inner membrane (stage IIIb).…”
mentioning
confidence: 49%
“…It then escorts the hydrophobic carrier across the intermembrane space, thus preventing its aggregation and acting as a chaperone (8,17,20,27,28). Subsequently, the precursor is inserted in the membrane by the 300-kDa TIM22 complex in a membrane potential-dependent manner (29,30).…”
mentioning
confidence: 99%
“…The hetero-hexameric TIM10 complex (20,25,28) is made exclusively of Tim9 and Tim10 that are necessary and sufficient to form the complex (20). They bind to each other with 1:1 stoichiometry (three molecules of Tim9 with three molecules of Tim10) and an affinity of 5 ϫ 10 6 M Ϫ1 (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, interaction with the TIM10 complex in this case does not commit the precursor to the TIM22 pathway. In fact two recent reports [36,37] have shown that the small Tim complexes can interact even with OM β-barrel proteins, thus expanding the idea that TIM10 functions as a low affinity generic chaperone of the mitochondrial IMS [38]. Commitment to one or the other membrane for insertion is probably dependent on specific substrate sequences that are recognized by the membrane-embedded insertion machinery TIM22 in the IM, or the sorting machinery SAM in the OM.…”
Section: Discussionmentioning
confidence: 99%